2021
DOI: 10.3389/fphar.2020.619200
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Natural Compounds and Circulating microRNA Expression Levels: Their Relationship Investigated in Healthy Subjects With Different Dietary Habits

Abstract: Diet has a strong influence on many physiological processes, which in turn have important implications on a variety of pathological conditions. In this respect, microRNAs (miRNAs), a class of small non-coding RNAs playing a relevant epigenetic role in controlling gene expression, may represent mediators between the dietary intake and the healthy status. Despite great advances in the field of nutri-epigenomics, it remains unclear how miRNA expression is modulated by the diet and, specifically, the intake of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 74 publications
1
33
0
1
Order By: Relevance
“…This is consistent with previous observations in all the three dietary groups between the estimated intake of particular nutrients and a set of plasma miRNAs. 14 A rising number of available data support the modification of faecal miRNA levels as a proxy of alteration and response occurring in the gut epithelium. 84 Indeed, the main source of faecal miRNAs is represented by intestinal epithelial cells, as described by Liu et al 23 Although, in the present study, we did not assess the cell of origins of the detected miRNAs, the analysis of the TissueAtlas and Roadmap Epigenomics data confirmed that most of the stool DEmiRNAs identified in the present study are expressed and active in the gut.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous observations in all the three dietary groups between the estimated intake of particular nutrients and a set of plasma miRNAs. 14 A rising number of available data support the modification of faecal miRNA levels as a proxy of alteration and response occurring in the gut epithelium. 84 Indeed, the main source of faecal miRNAs is represented by intestinal epithelial cells, as described by Liu et al 23 Although, in the present study, we did not assess the cell of origins of the detected miRNAs, the analysis of the TissueAtlas and Roadmap Epigenomics data confirmed that most of the stool DEmiRNAs identified in the present study are expressed and active in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recently, we clarified certain relationships between specific miRNA expression and the inclusion of specific nutrients in the diets of healthy individuals. 14 Dietary components can modulate the composition and function of the gut microbiome 15 16 and diets rich in fibres and poor in animal-based products (VN/VT regimes, Mediterranean diet) may drive a selection of specific taxa. [17][18][19] In parallel, a growing number of studies reported the association of a gut microbiome dysbiosis with several gastrointestinal and non-gastrointestinal diseases, including diabetes, 20 inflammatory bowel disease 21 and cancer.…”
Section: Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the intake of specific nutrients such as sodium and vitamins D and E is related to circulating miRNA profiles in healthy subjects. Similarly, a diet rich in polyphenols (resveratrol, ellagitannins, ellagic acid, epigallocatechin-3-gallate, genistein, curcumin, diindolylomethane) that maintains human health by tumor-protective and cancer-suppressive effects, and the high consumption of dietary fatty acids are associated with metabolic diseases via the regulation of miRNA expression [75][76][77]. In addition to dietary habits, the type of physical activity is significant, since it is known that long-term exercise alters plasma miRNAs levels in healthy young women.…”
Section: Circulating Mirnas As Promising Non-invasive Markersmentioning
confidence: 99%
“…In single or as clusters, dietary components can modulate miRNAs expression levels involved in regulating both physiological and pathological processes. [ 12 ] Different in vitro studies have been carried out to evaluate single nutrients' ability to affect miRNAs expression. [ 13,14 ] Cione and colleagues reviewed the in vitro effect of some grape polyphenols such as quercetin, epigallocatechin gallate, and resveratrol on miRNAs expression involved in inflammation and cancer.…”
Section: Introductionmentioning
confidence: 99%